The wallflower. vol. 7 - Hayakawa, Tomoko; Ury, David (New York, N.Y. : Ballantine Books, 2006)
Sunako's four roomies had better find a way to transform her into a lady quickly or her aunt may put them on the street. Also includes "Yuki versus the Abominable Snow Woman," an ill-fated trip to a haunted school, and the terror of the track meet.
Translated from the Japanese.
"Originally published in Japan in 2002 by Kodansha Ltd., Tokyo as Yamatonadeshiko Shiehihenge"--T.p. verso.
"A Del Rey Trade Paperback Original"--T.p. verso.
Includes a Japanese-language preview of volume 8.
Book reads right-to-left in the traditional Japanese format.
16+
Keywords: Spirits -- Comic books, strips, etc; Man-woman relationships -- Comic books, strips, etc; Ghost stories; Graphic novels